The Influence of Advertising and Electronic Word of Mouth On Purchasing Decision on The Shopee Marketplace - Febi Alin Purnama; H. Ari Arisman; Depy Muhamad Pauzy (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to determinate the effect of advertising and electronic word of mouth on purchasing decisions on the shopee marketplace (Survey on students of Universitas Perjuangan Tasikmalaya class of 2018). The research methode uses a quantitative method with a survey, the data used are primary and secondary data. The data analysis technique used is multiple linear regression analysis using SPPS v.25 software. The result of hyphothesis testing show that advertising and Electronic Word of Mouth have a significant effect on purchasing decisions in the shopee marketplace partialy and simultaneously.